Insight into binding characteristics of copper(II) with water-soluble organic matter emitted from biomass burning at various pH values using EEM–PARAFAC and two-dimensional correlation spectroscopy analysis. (September 2021) - Fan, Xingjun; Liu, Chao; Yu, Xufang; Wang, Yan; Song, Jianzhong; Xiao, Xin; Meng, Fande; Cai, Yongbing; Ji, Wenchao; Xie, Yue; Peng, Ping'an
Abstract: The metal-binding characteristics of water-soluble organic matter (WSOM) emitted from biomass burning (BB, i.e., rice straw (RS) and corn straw (CS)) with Cu(II) under various pH conditions (i.e., 3, 4.5, and 6) were comprehensively investigated. Two-dimensional correlation spectroscopy (2D-COS) and excitation–emission matrix (EEM) –PARAFAC analysis were applied to investigate the binding affinity and mechanism of BB WSOM. The results showed that pH was a sensitive factor affecting binding affinities of WSOM, and BB WSOMs were more susceptible to bind with Cu(II) at pH 6.0 than pH 4.5, followed by pH 3.0. Therefore, the Cu(II)-binding behaviors of BB WSOMs at pH 6.0 were then investigated in this study. The 2D-absorption-COS revealed that the preferential binding with Cu(II) was in the order short and long wavelengths (237–239 nm and 307–309 nm) > moderate wavelength (267–269 nm). The 2D-synchronous fluorescence-COS results suggested that protein-like substances generally exhibited a higher susceptibility and preferential interaction with Cu(II) than fulvic-like substances. EEM–PARAFAC analysis demonstrated that protein-like (C1) substances had a greater complexation ability than fulvic-like (C2) and humic-like (C3) substances for both BB WSOM. This indicated that protein-like substances within WSOM played dominant roles in the interaction with Cu(II). As a comparison, RS WSOM generally showed stronger complexation capacity than CS WSOM although they exhibited similar chemical properties and compositions. This suggested the occurrence of heterogeneous active metal-binding sites even within similar chromophores for different WSOM. The results enhanced our understanding of binding behaviors of BB WSOM with Cu(II) in relevant atmospheric environments. Graphical abstract: Image 1 Highlights: Metal-binding characteristics of BB WSOM were comprehensively investigated. WSOM bound with Cu(II) more strongly at high pH values than at low ones. Protein-like substances in WSOM displayed a preferential interaction with Cu(II). Tryptophan-like components exhibited higher binding capacity than humic-like ones.